Exposure to psychosocial risk factors in the context of work: a systematic review - Cláudia Fernandes; Anabela Pereira (Universidade de São Paulo, 2016)
ABSTRACT OBJECTIVE To analyze the scientific literature about the effects of exposure to psychosocial risk factors in work contexts. METHODS A systematic review was performed using the terms "psychosocial factors" AND "COPSOQ" in the databases PubMed, Medline, and Scopus. The period analyzed was from January 1, 2004 to June 30, 2012. We have included articles that used the Copenhagen Psychosocial Questionnaire (COPSOQ) as a measuring instrument of the psychosocial factors and the presentation of quantitative or qualitative results. German articles, psychometric studies or studies that did not analyze individual or work factors were excluded. RESULTS We included 22 articles in the analysis. Individual factors, such as gender, age, and socioeconomic status, were analyzed along with work-related factors such as labor demands, work organization and content, social relationships and leadership, work-individual interface, workplace values, justice and respect, personality, health and well-being, and offensive behaviors. We analyzed the sample type and the applied experimental designs. Some population groups, such as young people and migrants, are more vulnerable. The deteriorated working psychosocial environment is associated with physical health indicators and weak mental health. This environment is also a risk factor for the development of moderate to severe clinical conditions, predicting absenteeism or intention of leaving the job. CONCLUSIONS The literature shows the contribution of exposure to psychosocial risk factors in work environments and their impact on mental health and well-being of workers. It allows the design of practical interventions in the work context to be based on scientific evidences. Investigations in specific populations, such as industry, and studies with more robust designs are lacking.